Data‐based differential matched‐mode source depth estimation for a moving source. Issue 12 (12th November 2019) - Shi, Junjie; Sun, Dajun; Liu, Qingyu; Fu, Hongling; Zhao, Chong
Abstract : For locating a target moving in a more general track relative to the single receiver and at an ultra‐low frequency (<100 Hz) effectively, a differential matched‐mode method is proposed to estimate the depth of a moving source. It relies on the Hankel transform fast Fourier transform (FFT) to estimate the modal wavenumber difference spectrum for extracting source depth information. For the real data, the received signal as a function of the range is first processed by FFT per block to obtain the pressure field per range. Then these pressure fields are steered and beamformed according to the synthetic aperture created by the source motion to yield the modal wavenumber difference spectrum. A normalised source‐depth ambiguity function configured using these spectral peaks is applied to estimate the source depth with knowledge of the mode depth functions or nominal modal functions. Numerical simulation and experimental data all have tested this method with reasonable success especially when the source travels in a non‐radial direction relative to the single receiver.